Development of a multi-biomarker approach of genotoxicity on the three spined stickleback for aquatic biomonitoring application - Cant, Amélie; Bado-Nilles, Anne; Porcher, Jean Marc; Prygiel, Jean; Catteau, Audrey; Delahaut, Laurence; Turiès, Cyril; Geffard, Alain; Bonnard, Marc (HAL CCSD, 2022)
International audience The aquatic environment is considered as the receptacle of anthropogenicpressures, including chemical contamination as genotoxic compounds, which canimpact the health of aquatic species. Genotoxic substances may directly or indirectlyaffect the integrity of cell’s genetic material, which can lead to long-term mutagenic,carcinogenic or teratogenic effects. In this context, the measure of damages at differentgenomic scales may be relevant and provide an integrated view of the genotoxic risk ofexposed organism. The finality of our work is to propose their use as early-warningsignals of potential long-term alterations to population and ecosystem health.Genotoxicity assessment was performed on erythrocytes of the three- spinedstickleback by combining the measure of DNA integrity by the alkaline and Fpg(formamidopyrimidines DNA glycosylase)-modified comet assays and the measure ofvariations in nuclear DNA content by flow cytometry (FCM). In this sense, blood cells offish offer many advantages as cellular models as their ease of collection, gives a highdensity of erythrocytes already dissociated allowing to obtain multiple assays on thesame sample. The alkaline comet assay has been largely used with erythrocytes of fishto detect alkali-labile sites, DNA-double- and single- strand breaks. The Fpg-modifiedcomet assay has been optimized in the present study, which expand the comet assaysensitivity to oxidized pyrimidines. Furthermore, FCM may be applied to assess thevariations in the nuclear DNA content of a large population of cells and has alreadydemonstrated its relevance for detecting chromosomal damages in blood cells of fish.The presentation will detail results regarding the definition of baseline levels ofgenotoxicity biomarkers (DNA strand breaks, Fpg-sensitive sites, DNA content,erythrocyte mortality), which are useful in an ecotoxicological context. These biomarkershave been measured in various field context (active biomonitoring) and integrated in theexisting multi-biomarker approach of ...